Faliscan (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
The paper is devoted to Faliscan, an Indo-European language, belonging to the Italic branch and closely related to Latin, attested by approximately 300 inscriptions, coming from the ager faliscus (‘Faliscan territory’) in Lazio and dating from the 7 th to the 2 nd century BC. Specifically, the first part of the paper offers an overview of Faliscan epigraphy and language, updated in light of a review of the documents and studies on this topic. In the second part of the article, editorial and linguistic issues and perspectives are taken into consideration, with particular attention to the ‘Ceres-inscription’ and the Capenate inscriptions, respectively.
Keywords: Faliscan language; Faliscan epigraphy; Faliscan alphabet; 'Ceres inscription'; Capenate inscriptions